Penerapan Sistem Informasi Data Penduduk Dan Peta Ketahanan Pangan Pada Kampung Arul Gading - Nursharpina, Nursharpina; Hasfiyanda, Ovriza; Wahyuni, Maulia; Winnos, Hilman; Wahdiara, Wahdiara; Julisman, Julisman; Mukhlisin, Mulwin; Gemasih, Husna (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Food security is inseparable from the nature of food commodity production itself which is based on seasonality and fluctuation because it is very easily influenced by climate/weather. Such climate-influenced production behavior greatly affects national food availability. If the production behavior that is vulnerable to climate change is not complemented by a resilient food policy, it will cause many losses, both for producers and consumers, especially for small-scale producers and low-income consumers. The characteristics of perishable food commodities, including limited production land for farmers, inadequate agricultural supporting facilities and infrastructure, and weak harvest and post-harvest handling, encourage the Government to intervene by realizing food security policies.